STUDI EKSPERIMENTAL KARAKTERISTIK PERPINDAHANN KALOR PADA PIPA KONSENTRIK DENGAN PENAMBAHAN VORTEX GENERATOR TIPE BAFFLE DELTA, CIRCLE, DAN RACTANGLE GUNA MENGATASI ICING CONTAMINATED TAIL STALL - Galang Rivky Putra; Joni Kasmara; Gaguk Marausna; Farid Jayadi (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2022)
Horizontal stabilizer is the most important component of an aircraft in controlling the behavior of the aircraft while flying, if this component is disturbed it can result in loss of function in the elevator to pitch up and pitch down so that the plane can fall. One form of interference is icing caused by humidity and weather factors. The purpose of this research is to overcome the icing that occurs by using a heater. In this study, experimental methods with different variables were used to determine the effect of heating the contaminated airfoil on the double baffle delta, circle, and rectangle variations by utilizing the hot fluid produced from the heat gun and to determine the performance of convection heat transfer on baffle variations in heating the contaminated airfoil. The results of this study show that changing the shape of the baffle can increase the optimal convection heat transfer and create a turbulence effect, so that it can affect the performance of the heater. The shape of the baffle with the largest heat release is in the form of a baffle circle with a convective heat transfer value of 45.50 W, Reynold number value 3811.7, Nusselt number 14.80, convection heat transfer coefficient 18.44 W/m2.C, pressure drop 4.39 Pa, friction factor 0.0420.